Pengkajian Perspektif Karl Marx dalam Manajemen Pendidikan: Analisis terhadap Ketidaksetaraan Sosial dalam Sistem Pendidikan - Aisyah Syafitri; Silfia Hanani; Indra Devi; Muaddyl Akhyar; Ali Mustopa Yakub Simbolon (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
Education management plays an important role in making decisions about curriculum content and how education is planned and delivered. Inequality in access to education and curricular issues are two aspects of concern in Marx-inspired analyses of social inequality in education. The purpose of this research is to explain about the Assessment of Karl Marx's Perspective in Education Management: An Analysis of Social Inequality in the Education System. The method used in this study uses qualitative research procedures using a research approach in the form of a literature study. The sources of information in this research are reviewed from various novel sources of literature, research reports, scientific essays, theses, dissertations and posts both print and electronic related to the Study of Karl Marx's Perspective in Education Management: An Analysis of Social Inequality in the Education System. The results of this study suggest that addressing social inequalities in the education system, education management should prioritise fairer access for all students, regardless of their social and economic background. This could include providing financial aid, scholarships and support programmes for underprivileged students. In addition, education management needs to focus on improving the quality of education across the region. Improved school facilities, better teacher training and more relevant curriculum development are important steps in creating higher quality education. In this way, all students have the same opportunity to get a quality education.